2013
DOI: 10.1371/journal.pone.0081993
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an Acidic Endo-β-1,3-1,4-glucanase in Transgenic Maize Seed for Direct Utilization in Animal Feed

Abstract: BackgroundIncorporation of exogenous glucanase into animal feed is common practice to remove glucan, one of the anti-nutritional factors, for efficient nutrition absorption. The acidic endo-β-1,3-1,4-glucanase (Bgl7A) from Bispora sp. MEY-1 has excellent properties and represents a potential enzyme supplement to animal feed.Methodology/Principal FindingsHere we successfully developed a transgenic maize producing a high level of Bgl7AM (codon modified Bgl7A) by constructing a recombinant vector driven by the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…MEY‐1 was selected to be have an excellent properties and a potential supplement for poultry feed. Zhang et al . successfully developed transgenic maize producing a high β ‐glucanase activity (Bgl7A) in the seeds.…”
Section: Applications Of Fungal β‐13‐14‐glucanasesmentioning
confidence: 99%
See 1 more Smart Citation
“…MEY‐1 was selected to be have an excellent properties and a potential supplement for poultry feed. Zhang et al . successfully developed transgenic maize producing a high β ‐glucanase activity (Bgl7A) in the seeds.…”
Section: Applications Of Fungal β‐13‐14‐glucanasesmentioning
confidence: 99%
“…MEY-1 was selected to be have an excellent properties and a potential supplement for poultry feed. Zhang et al 66 successfully developed transgenic maize producing a high -glucanase activity (Bgl7A) in the seeds. Feeding trials have shown that the effectiveness of glucanase as a feed additive was maximized at approximately 30 000 units per kg of diets.…”
Section: Animal Feedmentioning
confidence: 99%
“…Feed pelleting was carried out as descripted previously [ 17 , 20 ]. α-Galactosidase activities and dry matter contents (DM) were measured before and after the pelleting process.…”
Section: Methodsmentioning
confidence: 99%
“…Maize as the main ingredient of animal feed (nearly 50%) is an ideal natural bioreactor in which a β-glucanase gene from Bispora sp. MEY-1 has been successfully expressed with the activity of 779,800 U/kg seeds [ 20 ]. The development of transgenic maize will not only reduce the loss of resources and simplify the production process, but also provide an environmentally friendly approach to produce feed enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Not only can food crops be biofortified by genetic engineering, they can also be designed to contain bioreactive compounds which have improved health benefits or reduce the risk of chronic diseases, such as cancer and heart disease [ 89 , 90 ]. The following section provides two examples of these “designer crops”.…”
Section: Biofortification Of Cropsmentioning
confidence: 99%